2021
DOI: 10.1007/s12185-021-03243-2
|View full text |Cite
|
Sign up to set email alerts
|

New-onset Evans syndrome associated with systemic lupus erythematosus after BNT162b2 mRNA COVID-19 vaccination

Abstract: Evans syndrome presents as concurrent autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP). Systemic lupus erythematosus (SLE) is the most frequent autoimmune disorder associated with Evans syndrome. We herein report a case of new-onset Evans syndrome associated with SLE after BNT162b2 mRNA coronavirus disease 2019 (COVID-19) vaccination in a 53-year-old woman. Blood examination at diagnosis showed hemolytic anemia with a positive Coombs test and thrombocytopenia. Hypocomplementemia and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…On the other hand, in a cohort of 56 patients with a history of AIHA, four elderly patients experienced a clinically significant hemoglobin reduction requiring treatment adjustment after receiving mRNA-based vaccines BNT162b2 or mRNA-1273. The same report described seven patients with autoimmune neutropenia who did not have exacerbations after receiving mRNA-based vaccines [110].…”
Section: Covid-19 Covid-19 Vaccination and Aiha Or Evans Syndromementioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, in a cohort of 56 patients with a history of AIHA, four elderly patients experienced a clinically significant hemoglobin reduction requiring treatment adjustment after receiving mRNA-based vaccines BNT162b2 or mRNA-1273. The same report described seven patients with autoimmune neutropenia who did not have exacerbations after receiving mRNA-based vaccines [110].…”
Section: Covid-19 Covid-19 Vaccination and Aiha Or Evans Syndromementioning
confidence: 94%
“…On the other hand, the number of statements documenting the association between COVID-19 vaccines and Evans syndrome is remarkably low (Table 3). To the best of our knowledge, only one of these cases is described in the literature, corresponding to a female patient who also presented with systemic lupus erythematosus (SLE) after being administered the BNT162b2 vaccine [110].…”
Section: Covid-19 Covid-19 Vaccination and Aiha Or Evans Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Anyway, to our knowledge, this is not the first evidence of the association of ES with SARS-CoV-2 vaccination. Hidaka et al have reported a new-onset ES with systemic lupus erythematosus after a second dose of BNT162b2 mRNA COVID-19 vaccination, quickly resolved with prednisolone 1 mg/kg/day [15]. Specifically, our case describes an isolated secondary ES after a single dose of SARS-CoV-2 vaccine, demonstrating a rapid resolution of AIHA although with the persistence of ITP, which generally tends to be more sensitive to immunosuppressive drugs than AIHA.…”
Section: Discussionmentioning
confidence: 58%
“…Complications such as hematuria, extensive petechial hemorrhage, subarachnoid hemorrhage [ 178 ], immune thrombocytopenia [ 179 , 180 , 181 , 182 , 183 ], Evans syndrome [ 184 ], acquired hemophilia [ 185 ], and factor XIII inhibitor [ 186 ] have been reported with the use of adenovirus vector and mRNA vaccines. In particular, when platelet transfusion is performed for hemorrhagic disease, examination to rule out VITT should always be performed, because with the presence of VITT in the background, the underlying condition may be aggravated after platelet transfusion.…”
Section: Sars-cov-2 Vaccination-associated Coagulopathymentioning
confidence: 99%